PEM water electrolysis cells with catalyst coating by atomic layer deposition. (16th November 2021) - Laube, A.; Hofer, A.; Ressel, S.; Chica, A.; Bachmann, J.; Struckmann, T.
Abstract: The limited annual mining capacity and high costs of platinum metal group catalysts (PMG) are confining the production of hydrogen from PEM electrolysis. Therefore, a significant reduction of catalyst needs is crucial to reduce system costs and increase production capacity. This study demonstrates the feasibility of a PEM water electrolysis cell design using porous transport electrodes (PTE) with catalyst coating by atomic layer deposition (ALD) and operation in 1 mol/L sulphuric acid at 60 °C. Though the catalyst loading has been reduced to 0.12 mg/cm 2 iridium on the anode and 0.28 mg/cm 2 platinum on the cathode, a current density of 168 mA/cm 2 and mean high mass activity of 1400 A/g iridium could be achieved at 1.7  V . The characterization of three high loading PTE cells is combined with a detailed overpotential analysis from polarization curve fits and demonstrates a reproducible cell setup. Further analysis steps show an increasing cell performance with increasing coating cycle numbers and the consistency of the anode performance in the three electrode setup with the complete cell. The ALD coated PTE design turns out to be a promising candidate for catalyst loading reduction in PEM electrolysis. Highlights: Demonstration of a cell design with porous transport electrodes and atomic layer deposition. Reduction of catalyst at high mass activity. Experimental characterization combined with a detailed overpotential analysis from polarization curve fits